Effect of magnetic fields on heavy metal and nutrient removal in leachate - Wan Mansor, Wan Salida (2006)
The capabilities of leachate treatment to achieve the allowable limit standards are well known to be universal problem. All kinds of technology treatment methods are used but still difficult to reach the minimum standard requirements. Magnetic technology is a physical treatment technique, which is commonly used in water processing industry. This situation attracts treatment to use the magnetic technology to further increase the leachate treatment capabilities. This study is mainly focused on the capability of the technology to increase the removal of heavy metals and nutrient. The settling of the treated leachate test, which was done, applied to the behavior of the first kinetic model and the settling time, found out to be most suitable after 60 minutes. The results of the test conclude that the capability of heavy metals and nutrient removal can be further increased using the flowing method with magnetic fields; and with different flow rate and circulation time. The study reveals that lower flow rate and higher circulation time will enhance the removal in leachate. Experimental design with a magnetic strength of 0.55 Tesla, a flow rate of 1 mL/s and circulation time at 7 hour shows that the concentrations of Cr, Fe, Mn and PO4 -3 were decreased. The percentage of Cr removal is 92.8 compared to 87.8 without magnet, so as Fe is 72.9 compared to 70.6, Mn is 50.6 compared to 45.5and PO4 -3 is 33.2 compared to 19.6. This study concluded that magnetic technology has the potential to be used to further increase the efficiency of leachate treatment by increasing the removal of heavy metals and nutrient.